Agent and system for improving water quality. - Mohamed Din, Mohamed Shariff; Md. Yusoff, Fatimah; Banerjee, Sanjoy; Khatoon , Helena (2009)

(untitled)
A preferred embodiment of the present invention relates to filtration and a purifying system to remove contaminants from water. Moreover, the system discloses utilization of beneficial microorganism to improve water quality. The system is said to provide effective and easy application as well as cost beneficial.